Interactional Metadiscourse used in Bloomberg International Debate - Riski Istiani; Dian Puspita (Linguistics and Literature Students' Journal, 2020)
In delivering an argument, several things must be known, such as the theme, the purpose, and the content of the argument in a debate. Since debate demands critical thinking, debaters need to consider their words’ choice in delivering their argument. In that case, this research aims to analyze the uses of interactional metadiscourse markers that are applied in the Bloomberg International Debate. In doing the analysis, the writers used the descriptive method and proposed Hyland’s theory (2005). As the result of the research, it shows that the most speaker who is producing interactional metadiscourse markers is Ella Cox, followed by John Allan and then Ndidie Okezie and finally Auday and Rus Ma. Although there are three speakers in each team (both proposition and opposition), it seems that the third person on each team only as support and the one who then summarizes the result of the debate for each team. Further, related to the uses of interactional metadiscourse, the most used of the interactional dimension markers is self-mention, followed by booster, hedges, and booster.Keywords: Bloomberg, critical thinking, debate, interactional metadiscourse, metadiscourse markers